Kebebasan Berpendapat Di Media Sosial Dalam Perspektif Hukum Pidana Di Indonesia - Riskiyastika, Devita; Tanuwijaya, Fanny; Wildana, Dina Tsalist (PMIH Untag Semarang, 2024)
Freedom of speech is one of the rights that individuals possess for expressing themselves, sharing opinions, and is protected by positive law in Indonesia. With the advancement of technology, public opinions are often shared through social media, where information can be quickly and easily obtained. Expressing opinions on social media may sometimes involve elements of defamation or insults toward others, which can lead to legal consequences. One case concerning defamation on social media is Decision Case Number 986/Pid.Sus/2021/PN Tjk. The research method used is normative juridical legal research. The research results indicate two legal issues to be examined. First, what are the differences in the elements of defamation offenses under the Electronic Information and Transactions Law and the Criminal Code? Second, has Decision Number 986/Pid.Sus/2021/PN Tjk aligned with the facts presented in the trial regarding defamation? The research findings suggest that the regulation of defamation in the Criminal Code is general, while in the Electronic Information and Transactions Law it is specific. The case of Decision Number 986/Pid.Sus/2021/PN Tjk does not align with the legal facts presented in the trial, as further analysis reveals that the more appropriate charge for the defendant would be the crime of defamation under Article 311 paragraph (1) of the Criminal Code.